E-LKPD Interaktif Berbasis Kontekstual Berbantuan Website Liveworksheets pada Muatan Matematika di Kelas III SD - Ni Ketut Sri Mahendri; I Made Citra Wibawa; Putu Ari Dharmayanti (Universitas Pendidikan Ganesha, 2024)
The lack of interactive media in learning makes students' mathematics learning outcomes low. Seeing this, this research aims to analyze the effectiveness of contextually based interactive E-LKPD assisted by the liveworksheets website on mathematics content in class III elementary school. This research uses the ADDIE model. Data collection methods using rating scale questionnaires and tests. The data collection instruments are questionnaire sheets and multiple-choice tests. The validity of the instruments that have been created is tested using the Gregory formula. The research subjects consisted of 2 experts, 3 teachers and 21 students. The data analysis techniques used are qualitative and quantitative data analysis. The research results showed that the feasibility of the product by material experts was (4.8), media experts were (4.65), and design experts were (4.8). Practicality by teachers is (4.8), and students are (4.48). The one sample t-test on student learning outcomes shows that contextually based interactive E-LKPD with the help of the live worksheets website on mathematical content is feasible, practical and effective for improving cognitive learning outcomes in the material of angles of plane shapes in class III of elementary school. This research implies that it is hoped that it will be able to add references for teachers making interactive LKPD for students.